Food quality in domestic markets of developing economies:A comparative study of two countries - Anneleen Vandeplas; Bart Minten (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
Food quality has become an important detfirminant of success in global food trade and growers for international markets have to continuously adjust to buyers' requirements. It is however not clear to what extent there is a demand for food quality - and how much buyers are willing to pay for it - in domestic food markets of developing economies. Based on unique comparable price and trader data in a poor country in Africa (Madagascar) and an emerging economy in Asia (India), we compare food quality and quality's pricing. We find significantly better quality and higher quality premiums (using revealed as well as stated preference methods) in India than in Madagascar. We explain these observed differences through a simple theoretical model, solely based on large average income gaps between the two countries.
Keywords: Q12; Q13; L15; 330; food quality; quality premiums; development